Developing an introduction to horticultural therapy course for college students - Lunday, Linda Carol (Kansas State University, 2009)
Educational opportunities in horticultural therapy at colleges and universities are currently experiencing a minimal level as compared to the time of their development in the early 1970’s. While there is an education decline in horticultural therapy, there is a rebirth of interest in this therapeutic modality taking place within the medical profession. Due to the lack of availability of university introductory-level horticultural therapy courses throughout the United States, it is important to ascertain what topics are needed for inclusion in an introductory course. A survey was sent to 13 horticultural therapy practitioners, 11 university instructors, and 8 students. Overall, responses of practitioners and professors were varied in their opinions. The one topic of importance in which they agreed was horticultural therapy definitions, as definitions for horticultural therapy, horticultural therapist, and horticultural therapy programs. A majority of horticultural therapy practitioners indicated that horticultural therapy history and theories are important topics for an introductory horticultural therapy course. A majority of the professors reported that horticultural therapy settings are a somewhat important topic. Topics of interest to students who had taken an introduction to horticultural therapy course included interaction with special populations (for example, elders, children, patients in physical rehabilitation), the use of adaptive gardening techniques and tools, and measuring the benefits of horticultural therapy. Topics of interest about which students wanted to learn more were ways in which to help each population through planned activities and how to reach horticultural therapy goals planned for patients and clients. Results of a literature search was conducted in which sources of information indicated that there have been declines in educational opportunities over time and a lack of growth in these opportunities. Based on the survey results and literature review, an introductory horticultural therapy course was developed. An introduction-type course is one that briefly introduces most, if not all, topics that will be studied in depth in more advanced courses. It should be designed in such a way that interests students and encourages them to continue their studies in the program. At the same time, the concerns and interests of the practitioners and professors need to be considered in the design of the course. As a result, the course was planned and includes the topics that are of interest to the participants in the surveys. The topics include horticultural therapy history, theories, definitions, program types, client/patient groups, settings, and the people-plant relationship.
Keywords: horticultural therapy; Introductory horticultural therapy course; people-plant relationship; horticultural therapy definitions; Kansas State University; horticultural therapy course development; Education, Higher (0745)